Słowiańskie strachy we współczesnej polskiej literaturze fantastycznej - Paulina Siedlecka-Jamiołkowska (Zagadnienia Rodzajów Literackich)
The article presents examples of the use of old Slavic beliefs by authors of contemporary Polish horror, including stories included in five anthologies published by Horror Masakra in 2016– 2023, in the unrelated Żertwa. Antologia słowiańskiego horroru, and the novel Gałęziste by Artur Urbanowicz. In contemporary Polish fantasy, after 1989, we can see a growing trend of interest of writers in old Slavic beliefs or their literary interpretation and re-creation. The first analysis of this phenomenon was Elżbieta Żukowska’s doctoral dissertation Religia dawnych Słowian we współczesnej polskiej prozie fantasy, which covers this subject in the years 1986–2011 and her research material consist of about fifty works inspired by Slavic mythology, but these are only fantasy texts. In the last decade, the number of such works has only increased significantly, which may be indicated by the fact that in the period 2012–2023 there are already about three hundred of such texts. Despite her insightful and accurate analyses, the researcher completely ignores “Slavic” horror, which is currently emerging as the second most popular medium of interest in pre-Christian beliefs in Polish literary fantasy, right after fantasy. The wealth of Slavic beliefs rediscovered today allows for the creation of many original and attractive stories, including those that cause nightmares. As the examples presented in the article have shown, “Slavic fears” have many faces, and many of them take the form of various creatures originating from the incredibly rich demonology of our ancestors. However, authors most often do not reach for the sophisticated sources of human fear, but for the most primal and universal ones, related to fear of untamed nature, fear of darkness and the unknown lurking in the darkness, or disgust at the sight of dirt, disease, blood and human entrails.